Product Creativity and Utilization of Cardboard and Batik Patchwork A Training Program for MSMEs in Serengan District Surakarta - Ipung Sri Purwanti Hery; Hartati Dyah Wahyuningsih; Hariyanti Hariyanti Hariyanti (IJECS: Indonesian Journal of Empowerment and Community Services, 2022)
MSMEs business are businesses run by individuals, households or small business entities that encourage the movement of Indonesia's economic development. In Surakarta, there are a lot of MSMEs, which have roles in maintaining the economy during the Covid 19 pandemic. The development of MSMEs is a serious problem to be handled. There is in fact a good work to get the opportunities to maintain their business, such as reducing the waste of boxes and patchwork. The research team took the initiative on how to process cardboard and patchwork waste into tissue boxes that would make the polluted trashes have more added values. The team benefited this opportunity to provide training to MSMEs on how to make used of cardboard and batik patchwork into beautiful tissue boxes and nice crafts that can generate income and maintain the family economy. Thus, it helps government of Serengan District, Surakarta in developing MSMs activities.